Mpox: Epidemiological profile and factors associated with complications in the Isangi Territory, Democratic Republic of the Congo - KOMBOZI, Dieu-Merci; Feruzi, V. K.; Amosi, Guld; Lwanga, Kakule; Bolekaleka, Valentin; Longembe, Basandja; Tepungipame, Tagoto; Likwela, Losimba (Orapuh Journal, 2025)
Introduction The Mpox outbreak in non-endemic regions has recently attracted global attention. The Isangi Territory has experienced Mpox epidemic outbreaks in recent years, during which several deaths were reported. Purpose This study aimed to describe the epidemiological profile of Mpox and to identify the factors associated with the occurrence of complications. Methods An analytical cross-sectional study was conducted in three health zones of the Isangi Territory, covering the period from January 2023 to January 2024. It included 230 patients with PCR-confirmed Mpox infection. Factors associated with the occurrence of complications were analysed using Odds Ratios (OR) and 95% Confidence Intervals (CI). Results The annual incidence of Mpox was 0.043%, with a case fatality rate of 4.7%. The median age of patients was 20 years (IQR: 5–25), and females were slightly more affected (54.8%). Most cases (99%) had no history of smallpox vaccination. Significant risk factors for complications included: age under 17 years (OR = 61.7, 95% CI: 24.8–160.1, p < 0.001), history of malnutrition and/or measles (OR = 34.9, 95% CI: 11.7–134.5, p < 0.001), seeking initial care from prayer sites or traditional healers (OR = 34.4, 95% CI: 15.0–82.7, p < 0.001), low socioeconomic status (OR = 4.7, 95% CI: 1.3–25.8, p = 0.009), and a higher education level was found to be a protective factor (OR = 0.4, 95% CI: 0.2–0.7, p = 0.001). Conclusion Complications related to Mpox infection are associated with sociodemographic, economic, and healthcare-related factors. Targeted interventions are needed to address each of these risk elements.